Pengaruh E-Service Quality terhadap Kepuasan Penjual Online pada Situs Bukalapak.Com - Bayu Rakasiwie; Sri Rejeki Ekasasi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to analyze the effect of e-service quality (electronic service quality) on online seller’s satisfaction on the Bukalapak.com site. The population of this study is the site customers who are online sellers with a total of 70 sellers as respondents. Data was obtained through a questionnaire using Google form. Multiple linear regression equation was used to determine the effect between the independent and dependent variables. Prior to data processing, validity, reliability, normality, multicollinearity, heteroscedasticity, and goodness-of-fit tests were conducted. Hypothesis testing is done by t test and R2 termination test. The results showed that the variables of efficiency, reliability, privacy and responsiveness had a positive and significant effect on online seller’s satisfaction on the Bukalapak.com site.